1991
DOI: 10.1073/pnas.88.9.3545
|View full text |Cite
|
Sign up to set email alerts
|

Trans-seasonal action of androgen in the control of spring courtship behavior in male red-sided garter snakes.

Abstract: Gonadal steroids have traditionally been found to have short-term effects on the mating behavior of adult vertebrates, such that increased steroid hormone levels influence behavior over the course of a few days. Long-term effects also have been observed in which embryonic exposure to steroid hormone influences the sexual behavior of adults. The generality of the paradigms that have resulted from this work must be viewed with caution as all of the species studied exhibit a particular reproductive pattern. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…This restriction does not appear to be necessary in female snakes unless the low level of estrogen remaining in ovariectomized animals is sufficient to induce genomic, long-term changes. An alternative mechanism may be that of "gene memory", where estrogen can exert long-term effects on the genome that persist in the absence of the steroid and then elicit a more rapid response when the stimulus is re-instated (Burch and Evans 1986;Hache et al 1987;Crews 1991;Pfaff et al 1994).…”
Section: Receptivitymentioning
confidence: 99%
See 2 more Smart Citations
“…This restriction does not appear to be necessary in female snakes unless the low level of estrogen remaining in ovariectomized animals is sufficient to induce genomic, long-term changes. An alternative mechanism may be that of "gene memory", where estrogen can exert long-term effects on the genome that persist in the absence of the steroid and then elicit a more rapid response when the stimulus is re-instated (Burch and Evans 1986;Hache et al 1987;Crews 1991;Pfaff et al 1994).…”
Section: Receptivitymentioning
confidence: 99%
“…However, although independent of androgenic modulation of courtship behavior in the relative short term (i.e. 1 2 years), males do require periodic exposure to testosterone (T) for the continued seasonal expression of behavior (Crews 1991). For example, males that have been gonadectomized 3~4 years no longer exhibit courtship behavior even after exposure to hibernation conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crews and Garstka, 1982). In this dissociated breeder, reproductive behavior does not coincide with peak gonadal activity (Crews, 1984;Crews, 1991;Crews et al, 1984). Rather, mating occurs while plasma sex steroid concentrations are declining, gonads are regressed, and glucocorticoid levels are high (Aleksiuk and Gregory, 1974;Crews 1984;Crews et al, 1984;Whittier et al, 1987b).…”
Section: Introductionmentioning
confidence: 99%
“…In male garter snakes, courtship behavior in the spring occurs when the levels of circulating sex hormones are low; testicular growth docs not occur until the summer, long after all sexual activity has ceased [Crews et al. 1984;Crews, 1990], Recently it has been shown that the testosterone surge associated with testicular recrudescence in the summer effects brain activity such that males respond appropriately to attractive females on emer gence from hibernation the following sping [Crews, 1991). If sexual behavior can be dissociated from gonadal activity, can the brain areas known to be involved in the control of sexual behavior (data from species with an associated reproductive pattern) be similarly dissociated?…”
Section: Introductionmentioning
confidence: 99%